PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA TOUR AGENT CAH PANTAI - Sri Rahayu Puspita Sari; Ratih Fitri Yatun (Asosiasi Dosen Muda Indonesia, 2023)
The tourism sector is one of the pillars of the Indonesian economy and a major foreign exchange earner. Natural and cultural wealth is an important component of tourism in Indonesia. The large number of tourist objects opens up opportunities for businesses in the tourism sector, one of which is a travel agent. The aim of this research is to find out and analyze the effect of promotion and service quality on customer satisfaction at Cah Pantai travel agents partially or simultaneously. The data used in this study are primary data using a questionnaire instrument of 100 respondents. The sampling method in this study was non-probability sampling with a purposive sampling technique or sampling based on certain characteristics. The tests carried out consisted of validity, reliability, classical assumptions, multiple linear regression, t test, f test, and the coefficient of determination. The results of this study indicate that Promotion and Service Quality indirectly affect customer satisfaction at the Cah Pantai Tour Agent. Promotion and Service Quality together influence customer satisfaction at Cah Pantai tour agents.